Human and The Challenges of Islamic Education: Interpretation Studies on Human Concepts - Majid, M. Abdul; Bulqois, Nabilah (Jurnal Pendidikan dan Konseling (JPDK), 2022)
This study aims to identify and analyze human and the challenges of Islamic education. The discussion is focused on how the nature and characteristics of humans as individuals in the world of education? How could Islamic education be able to interact with humans? How can Islamic Education be able to touch the dimensions of human nature and characteristics? The data was obtained through a literature study and then analyzed for its relevance to the actual facts which are happening today. The existence of distortions and deviations from nature as well as moral decadence has caused symptoms as if forgetting the essence of the human being himself. Thus, Islamic Education is a strategic point in terms of moral development so that moral values ??and ethics will be found in it. While the study of interpretation of al-Qur’an as an answer to rediscover the nature and characteristics of humans as the main actors in al-Qur’an itself and the role of humans in this matter. Therefore, Islamic education is important to implement all of those problems which could be able to restore human nature as a superior being.